The Pathology and Physiology of Ileostomy - Ma, Haitao; Li, Xiaolong; Yang, Hua; Qiu, Yuan; Xiao, Weidong (Frontiers in Nutrition, 2022)
An ileostomy is a surgery that is commonly performed to protect low pelvic anastomoses or prevent high-risk anastomotic leakages. However, various postoperative complications remain of major concern. After an ileostomy, the distal intestinal segment is left open for an extended period and is in a non-functional state. Consequently, the intestinal mucosa, smooth muscle, and microbiota undergo significant changes that are closely related to postoperative recovery and complications. A systematic description of these changes is necessary to understand the relationship among them and take more effective measures for postoperative intervention.